2023
DOI: 10.3847/1538-4357/aca535
|View full text |Cite
|
Sign up to set email alerts
|

Wide-band Timing of the Parkes Pulsar Timing Array UWL Data

Abstract: In 2018 an ultra–wide-bandwidth low-frequency (UWL) receiver was installed on the 64 m Parkes Radio Telescope, enabling observations with an instantaneous frequency coverage from 704 to 4032 MHz. Here we present the analysis of a 3 yr data set of 35 ms pulsars observed with the UWL by the Parkes Pulsar Timing Array, using wide-band timing methods. The two key differences compared to typical narrowband methods are (1) generation of two-dimensional templates accounting for pulse shape evolution with frequency an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Figure 3). This feature was already reported in Tarafdar et al (2022) and is also shown in Curyło et al (2023) that used, respectively, the first data release of InPTA and the ultra-wide-bandwidth lowfrequency data from PPTA. Interestingly, we do not observe any associated impact on the RN posterior distributions.…”
Section: Psr J1909−3744supporting
confidence: 78%
“…Figure 3). This feature was already reported in Tarafdar et al (2022) and is also shown in Curyło et al (2023) that used, respectively, the first data release of InPTA and the ultra-wide-bandwidth lowfrequency data from PPTA. Interestingly, we do not observe any associated impact on the RN posterior distributions.…”
Section: Psr J1909−3744supporting
confidence: 78%
“…We fit initial timing models using TEMPO2 (Edwards et al 2006), beginning from the timing analyses of the previous data releases (Reardon et al 2016(Reardon et al , 2021. For new pulsars added to the PPTA since the second data release (PPTA-DR2), we use the initial timing models from Curyło et al (2023). For four pulsars we required updates to the timing models.…”
Section: Methods and Noise Model Componentsmentioning
confidence: 99%
“…In the case of PSR J0437−4715, we first formed the invariant interval c (Britton 2000) of the profile prior to forming standard templates and hence ToAs. In this data release, we first followed the method presented by Pennucci et al (2014) to form wide-band profile portraits (Curyło et al 2023). We created one-dimensional templates for each channel across the eight sub-bands by evaluating the wide-band portrait model at the channel centre frequency.…”
Section: Timing Measurements From Wide-band Observationsmentioning
confidence: 99%
“…We formed timing residuals initially using the timing ephemerides presented by Reardon et al (2021) and Curyło et al (2023), with the TT(BIPM2020) reference timescale published by the Bureau International des Poids et Mesures (BIPM) and the Jet Propulsion Laboratory Solar System ephemeris DE436. The wideband nature of the observations means that the ToA precision in each sub-band can vary with the scintillation state of the pulsar.…”
Section: Timing Measurements From Wide-band Observationsmentioning
confidence: 99%
See 1 more Smart Citation